(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Big Data technologies have attracted much attention among researchers due to their potential to handle large amounts of data. Big Data continues to become a hot topic of research in the agricultural field. Recent developments in the field of technology have led to a renewed interest in the field of smart agriculture. The current smart agricultural system produces and depends on large amounts of data, yet, it is hard to process the vast amounts of data using traditional data analysis systems Thus, for numerous possibilities and powerful data processing capabilities.The internet, sensor devices and data analytic paves the way for better performance, advanced resources planning and enhanced production in all industries. The agriculture is the most important and essential need for the world to invest and make research to strengthen the yield, crop disease control, farming community and advance agricultural production.In this paper, there is a brief description about big data and its techniques involved in agriculture.